SIMPSON'S FORENSIC MEDICINE - Payne-James, Jason; Jones, Richard (CRC Press, 2020)
Prestigious and authoritative, this fully updated fourteenth edition of Simpson's Forensic Medicine remains a classic; one of the world's leading introductory texts in the field of forensic medicine. It presents all that the generalist or student needs to know about the interface between medicine and the law, including forensic toxicology, forensic science, forensic odontology, forensic anthropology and both the legal obligations and ethical responsibilities of those working in forensic settings.